2009
DOI: 10.1186/1471-2458-9-54
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to kidney donation among primary care patients in rural Crete, Greece

Abstract: Background: In Greece, there is limited research on issues related to organ donation, and the low rate of registration as donors requires explanation. This study reports the findings of a survey of knowledge and attitudes to kidney donation among primary care patients in rural Crete, Greece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
2
19
0
1
Order By: Relevance
“…Although the major focus of research has been on the variations in attitudes to donation and donation rates among ethnic minorities, we observed that primary care users living in rural and remote mountain areas in Crete have more negative attitudes to donation compared with more urban areas [30]. This observation supports the hypothesis that the socio-demographic characteristics of communities may influence knowledge and attitudes to organ donation, with diversity in beliefs and attitudes extending beyond ethnic groups.…”
Section: Discussionsupporting
confidence: 78%
“…Although the major focus of research has been on the variations in attitudes to donation and donation rates among ethnic minorities, we observed that primary care users living in rural and remote mountain areas in Crete have more negative attitudes to donation compared with more urban areas [30]. This observation supports the hypothesis that the socio-demographic characteristics of communities may influence knowledge and attitudes to organ donation, with diversity in beliefs and attitudes extending beyond ethnic groups.…”
Section: Discussionsupporting
confidence: 78%
“…3 Furthermore, it has been hypothesized that sociocultural features of communities may greatly influence perceptions of organ donation enhancing diversity. 4 For these reasons we agree with Chatterjee et al 1 that allowing funds to support activities that respond to the local context may be more effective than systemic changes.…”
Section: Organ Donation and New Policies: Do We Need To Act Less Genesupporting
confidence: 83%
“…These views were supported by Symvoulakis, demonstrating that the implementation of family practice-driven information and educational campaigns about organ donation and transplantation has the potential to increase the numbers of new donors. 12 MISTRUST Distorted beliefs, negative or ambivalent attitudes, indifference, and lack of knowledge and trust in healthcare systems are often more harmful than chronic diseases, and potentially cost lives. 12 One of the reasons for this reticence could be that many Asian countries do not have a successful deceased organ donation programme in place and organ donation is considered a Western concept.…”
Section: Reflection Pointsmentioning
confidence: 99%